The Effects on Consumption Patterns of Replacing Housing Programs with Cash Grants - Early, Dirk W.; Olsen, Edgar O. (Housing policy debate, 2025)
This paper estimates how replacing low-income housing programs with equally costly cash grants would change the consumption patterns of recipients. Based on American Housing Survey data and evidence on the cost-effectiveness of different types of assistance, the results suggest that housing voucher recipients consumed 15% more housing services and 12% fewer other goods than they would have consumed had they received equally costly cash grants. Occupants of subsidized projects lived in housing about as good as they would have chosen with cash grants but consumed substantially fewer other goods. Owing to their cost inefficiencies, programs of project-based housing assistance have led to less consumption of both goods than would result from cash grants for substantial fractions of their participants. Approximately two thirds of public housing tenants and more than a third of recipients of other forms of project-based housing assistance occupy worse housing and consume fewer other goods than they would with equally costly cash grants. These findings make a strong case for the use of cash assistance rather than project-based housing assistance to help low-income households and question whether voucher's modest improvement in housing conditions compared with cash grants justifies its extra administrative costs and the burden it places on households to find a landlord willing to accept a voucher.